THE EQUAL AUTHENTICITY OF OFFICIAL LANGUAGE VERSIONS OF EUROPEAN LEGISLATION IN LIGHT OF THEIR CONSIDERATION BY THE COURT OF JUSTICE OF THE EUROPEAN UNION - PALUSZEK, Karolina (Comparative Legilinguistics, 2014)
The aim of the paper is to analyse the judgments of the Court of Justice of the European Union in order to determine whether all official language versions of EU legislation are considered in the course of interpretation. The Court itself has stated in many of its judgments1 that all official versions should be taken into account in the interpretation process as they all have an equally authentic character. Moreover, the comparison of all official language versions is a common feature for all methods of reconciliation of differences between various language versions that had been distinguished in literature. The author has examined 80 judgments in order to determine whether the comparison of all language versions really forms an important part of the interpretation conducted by the Court, or if it should be regarded as an unfulfilled wish expressed by the scholars and the Court itself.